2018
DOI: 10.3389/fnhum.2018.00066
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Experience of Time in Depression—Evidence from Content Analysis

Abstract: Disturbances in the experience of time have been a commonly reported feature of depressive disorders since the beginning of modern psychiatry and psychological research. However, qualitative research approaches to investigate the phenomenon are rarely used. We employed content analysis to investigate disturbances of time experience in Major Depressive Disorder. Our analysis from 25 participants showed that individuals with Major Depressive Disorder subjectively seem to have lost the ability to influence or cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 65 publications
3
44
0
Order By: Relevance
“…This consideration demonstrates the interconnectedness of structure and passage of time into an ongoing structured directedness (Kupke, 2007;Kupke & Vogeley, 2009;Vogel et al, 2018a). Accordingly, it may be reasoned, that changes in the experience of the passage of time directly reflect changes of experience of the three dimensions of time (Vogel et al, 2018a;Vogel et al, 2018b). Vice versa, this observation explains the vulnerability of individuals with ASD to disturbances of their routines, a clinical feature commonly observed and described by the primary symptom of "restricted, repetitive patterns of behavior, interests, or activities" (American Psychiatric Association 2013, p.50).…”
Section: The Experience Of Structure Of Timementioning
confidence: 96%
See 2 more Smart Citations
“…This consideration demonstrates the interconnectedness of structure and passage of time into an ongoing structured directedness (Kupke, 2007;Kupke & Vogeley, 2009;Vogel et al, 2018a). Accordingly, it may be reasoned, that changes in the experience of the passage of time directly reflect changes of experience of the three dimensions of time (Vogel et al, 2018a;Vogel et al, 2018b). Vice versa, this observation explains the vulnerability of individuals with ASD to disturbances of their routines, a clinical feature commonly observed and described by the primary symptom of "restricted, repetitive patterns of behavior, interests, or activities" (American Psychiatric Association 2013, p.50).…”
Section: The Experience Of Structure Of Timementioning
confidence: 96%
“…No time limits were given in order to guarantee data adequacy through proper data saturation (Sandelowski, M., 1995;Pope, C. et al 2000;Mason, M., 2010;Glaser B., & Strauss A., 2017). The TQ has been successfully used in two recent studies (Vogel et al, 2018a;Vogel et al, 2018b) and been demonstrated to sufficiently address both passage and structure of time with differential diagnostic resolution.…”
Section: The Time Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…As our second example, depressive episodes have been described by psychopathologists investigating the experience of time as being characterized by a “disturbance of becoming” or a “blocked future” ( Straus, 1928 ; von Gebsattel, 1954a , b ; Fuchs, 2013 ; Stanghellini et al, 2017 ; Vogel et al, 2018 ). Symptoms such as loss of interest, decreased affective reactivity, depressed mood, and emotionlessness, as well as psychomotor retardation, have been linked to this conceptual phenomenon ( Stanghellini et al, 2017 ; Vogel et al, 2018 ). Patients during major depressive episodes are thought to have lost the biologically anchored strive toward the future, rendering them unable to form emotional connections and to pursue or even form goals ( Straus, 1928 ).…”
Section: Enduring Situated Cognition and Psychopathologymentioning
confidence: 99%
“…Indeed, MDD patients often complain that subjective time is going by at a reduced pace compared with physical time (Gallagher, 2012;Ratcliffe, 2012;Vogel et al 2018). This perturbed time awareness has led to a systematic investigation of time 'perception' using quantitative methods requiring an explicit judgment about durations.…”
Section: Introductionmentioning
confidence: 99%